2016
DOI: 10.1186/s12885-016-2529-1
|View full text |Cite
|
Sign up to set email alerts
|

Pleural fluid osteopontin, vascular endothelial growth factor, and urokinase-type plasminogen activator levels as predictors of pleurodesis outcome and prognosticators in patients with malignant pleural effusion: a prospective cohort study

Abstract: BackgroundRapidly growing cancer cells secrete growth-promoting polypeptides and have increased proteolytic activity, contributing to tumor progression and metastasis. Their presentation in malignant pleural effusion (MPE) and their predictive value for the outcome of pleurodesis and survival were studied.MethodsBetween February 2011 and March 2012, MPE samples were prospectively collected from 61 patients. Twenty-five patients with non-malignant pleural effusion in the same period were included as controls. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…Ikeda et al measured the estrogen concentrations in the noncancerous peripheral lung tissue using liquid chromatography/electrospray tandem mass spectrometry in the postmenopausal female patients with synchronous multiple lung adenocarcinomas, and found a significantly higher level than the control cases with a single lung adenocarcinoma [ 78 ] ( Figure 1 ). Our study of the malignant pleural effusion of lung adenocarcinoma revealed that some postmenopausal women had extraordinarily high pleural fluid estradiol concentrations, and there was no correlation between the pleural fluid concentrations of estradiol and the vascular endothelial growth factor, a marker of pleural vascular hyperpermeability [ 79 ]. In addition, the EGFR wild-type lung adenocarcinoma is probably an estrogen-dependent carcinoma, as a higher expression and potent poor prognosticator of aromatase and the ERβ in the group [ 62 ].…”
Section: Estrogen Receptor In Lung Cancermentioning
confidence: 99%
“…Ikeda et al measured the estrogen concentrations in the noncancerous peripheral lung tissue using liquid chromatography/electrospray tandem mass spectrometry in the postmenopausal female patients with synchronous multiple lung adenocarcinomas, and found a significantly higher level than the control cases with a single lung adenocarcinoma [ 78 ] ( Figure 1 ). Our study of the malignant pleural effusion of lung adenocarcinoma revealed that some postmenopausal women had extraordinarily high pleural fluid estradiol concentrations, and there was no correlation between the pleural fluid concentrations of estradiol and the vascular endothelial growth factor, a marker of pleural vascular hyperpermeability [ 79 ]. In addition, the EGFR wild-type lung adenocarcinoma is probably an estrogen-dependent carcinoma, as a higher expression and potent poor prognosticator of aromatase and the ERβ in the group [ 62 ].…”
Section: Estrogen Receptor In Lung Cancermentioning
confidence: 99%
“…Two randomized trials recently analyzed MPE recurrence. The TIME 1 randomized trial reported that pleurodesis through 12 French chest tube is more associated with higher MPE recurrence after 3 months than 24 French chest tube (30% vs. 24% difference, −6%; 1-sided 95% CI, −20% to ∞; P=0.14 for noninferiority) (21 (24). As far as we know, our study is the first to evaluate risk factors for MPE recurrence only in NSCLC patients.…”
Section: Discussionmentioning
confidence: 81%
“…The results indicated that local pleural administration of bevacizumab plus cisplatin, alongside the systemic administration of paclitaxel, resulted in a much higher ORR (83.3 vs. 50.0%; P<0.05), compared with that in patients who received systemic administration of paclitaxel plus local cisplatin only ( 75 ). Patients in the first group demonstrated a significant reduction in the amount of pleural effusion, accompanied with a markedly improved quality of life, and tolerated the treatment well ( 75 ). Substantial additional clinical studies have all reported that bevacizumab is safe and effective for the treatment of MPE in patients with NSCLC ( Table III ) ( 76 – 82 ).…”
Section: Vegf-targeted Strategies For the Management Of Mpe In Patienmentioning
confidence: 96%
“…Data from two retrospective studies also confirmed that bevacizumab combined with chemotherapy drugs through intravenous injection can effectively control MPE in patients with nonsquamous NSCLC, with a MPE control rate of 92.3% and a MPE release rate of ≤71.4% ( 4 ). The efficacy of bevacizumab combined with platinum through local pleural administration in the treatment of MPE was investigated by Hsu et al ( 75 ). The results indicated that local pleural administration of bevacizumab plus cisplatin, alongside the systemic administration of paclitaxel, resulted in a much higher ORR (83.3 vs. 50.0%; P<0.05), compared with that in patients who received systemic administration of paclitaxel plus local cisplatin only ( 75 ).…”
Section: Vegf-targeted Strategies For the Management Of Mpe In Patienmentioning
confidence: 99%
See 1 more Smart Citation